2019
DOI: 10.1186/s40644-019-0229-1
|View full text |Cite
|
Sign up to set email alerts
|

Does establishing a preoperative nomogram including ultrasonographic findings help predict the likelihood of malignancy in patients with microcalcifications?

Abstract: Background Mammography (MG) is highly sensitive for detecting microcalcifications, but has low specificity. This study investigates whether establishing a preoperative nomogram including ultrasonographic findings can help predict the likelihood of malignancy in patients with mammographic microcalcification. Methods Between May 2012 and January 2017, 475 patients with suspicious microcalcifications detected on MG underwent ultrasonography (US). The χ 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 25 publications
2
11
0
Order By: Relevance
“…Previous studies have demonstrated the importance of menopausal status and age in breast cancer assessment. 4,11,15 In our research, the malignancy rate of patients older than 60 years was higher than that of younger patients. Similar results were reported by Oligane et al, 4 who found that patients younger than 50 years had a lower malignancy rate.…”
Section: Figurementioning
confidence: 43%
See 3 more Smart Citations
“…Previous studies have demonstrated the importance of menopausal status and age in breast cancer assessment. 4,11,15 In our research, the malignancy rate of patients older than 60 years was higher than that of younger patients. Similar results were reported by Oligane et al, 4 who found that patients younger than 50 years had a lower malignancy rate.…”
Section: Figurementioning
confidence: 43%
“…Distribution and morphology are recognized as independent influencing factors of calcifications. 4,5,11,17 Generally, the malignancy rate of calcifications with only one pure morphology is lower than that of calcifications with more than one type of suspicious morphology. 14 Previous studies on the PPVs of morphology and distribution descriptors demonstrated an increasing trend toward malignancy from amorphous/coarse heterogeneous to fine pleomorphic/fine linear/fine-linear branching microcalcifications and from regional/grouped to segmental/linear distribution.…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…[10][11][12] So far, nomograms have been established in the majority of cancer types. [10][11][12][13] For instance, Guo et al developed an USbased nomogram to improve the diagnostic accuracy of the identification of malignant thyroid nodules; 14 Qiu et al established and validated a nomogram to predict the probability of axillary lymph node metastasis as a preoperative tool to support clinical decision-making. 15 To the best of our knowledge, this study is the first attempt to develop and validate a nomogram based on US parameters as well as clinical risk factors to predict malignant STTs.…”
Section: Introductionmentioning
confidence: 99%